Friction Stir Welding of Dissimilar AA6061-T6 to AZ31B-H24 Alloys - Saldaña-Garcés,Rocio (2020)
Abstract: Friction Stir Welding (FSW) is a solid-state joining process that uses a non-consumable tool to join two facing workpieces without melting the workpiece material. FSW is predominantly used for welding lightweight materials such as aluminum and magnesium alloys. In the present investigation, AA6061-T6 and AZ31B-H24 alloys were joined by FSW using the following parameters: rotational speed of 400, 800, 1200 and 1600 rpm, welding speed of 30 and 60 mm/min and tilt angle of 1° and 3°. In some cases, a tool offset of 1 mm was used into the Mg-based alloy. Microstructural characteristics of the weld joints were analyzed by optical microscopy and scanning electron microscopy. The experimental results show that dissimilar welds can be obtained by placing the AA6061-T6 alloy on the advancing side under two processing conditions: i) without a tool offset using a welding speed of 30 mm/min, a rotational speed of 400 rpm and a tilt angle of 1° (M7) and ii) with a tool offset and a welding speed of 30 mm/min, using a rotational speed of 1200 rpm and a tilt angle of 3° (M3). Al3Mg2 and Al12Mg17 intermetallic compounds were observed in the stir zone. Hardness and tensile strength of joints M7 varied from 76 to 129 HV, and 88.2 MPa respectively, and these properties varied from 95 to 153 HV, and 18.95 MPa in joints M3.